Cross-Sectional Study of Burnout among a Group of Egyptian Oncologists at Ain Shams University - Ramy Ghali; Dina Boulos; Mohamed Alorabi (Research in Oncology, 2019)
Background: Oncologists are at risk of developing burn out syndrome due to many stressors they may face. Aim: To determine the level of burnout in a cohort of clinical oncologists working in an Egyptian university hospital. Methods: Fifty-two clinical oncologists were invited to participate in the study. Burnout was assessed using the Arabic version of Maslach Burnout Inventory Human Services Survey (MBI-HSS). Results: The response rate was 90% (47/52).  The majority (70%) of responders were young oncologists and 62% had >10 years experience in the oncology field. Females represented 52% of them and 62% were married. The MBI-HSS scores indicated that 72% of participants had burnout on the emotional exhaustion (EE) scale, 49% on the depersonalization (DP) scale and 38% on the personal accomplishment (PA) scale. A significantly lower PA score was associated with female gender, being single, viewing vacation time as insufficient, and an experience duration <10 years in oncology (p = 0.01, 0.01, 0.03, and 0.02; respectively). The preference not to choose again oncology as a career was also associated with significantly lower PA score and higher EE score (p=0.02 and 0.001; respectively). Conclusion: The surveyed oncologists experienced high burnout. Larger studies are needed in order to assess the burden of the problem and to develop evidence-based interventions to reduce it.